2015
DOI: 10.1002/app.43266
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of organosoluble and transparent polyimides containing bulky substituents and noncoplanar structures

Abstract: A new diamine monomer, 3,3 0 -diisopropyl-4,4 0 -diaminophenyl-4 00 -phenyltouene, was designed, synthesized, and then polymerized with five commercial dianhydrides to obtain a series of novel polyimides via a one-step method. The obtained polymers showed excellent solubility in most common solvents, even in low-boiling solvents, such as chloroform, dichloromethane, and tetrahydrofuran. They exhibited a high thermal stability with the glass-transition temperature in the range 262-3188C and 10% weight loss temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
1
16
1
Order By: Relevance
“…The higher T g of PI‐6 and PI‐7 than other PIs except PI‐1 could be due to the rigid alicyclic structures in CBDA and BTA. Compared with PIs having other symmetric bulky isopropyl and biphenyl moieties, all T g values for our PIs were found to be higher by at least 50 °C …”
Section: Resultscontrasting
confidence: 52%
See 2 more Smart Citations
“…The higher T g of PI‐6 and PI‐7 than other PIs except PI‐1 could be due to the rigid alicyclic structures in CBDA and BTA. Compared with PIs having other symmetric bulky isopropyl and biphenyl moieties, all T g values for our PIs were found to be higher by at least 50 °C …”
Section: Resultscontrasting
confidence: 52%
“…Different approaches have been reported in order to improve the transmittance and solubility of PI films, including the incorporation of flexible linkages, fluorinated structures, unsymmetrical or noncoplanar structures, alicyclic structures in the backbone and the introduction of bulky pendant substituents to the polymer chains . On the other hand, the solubility and transparency of PI films could be improved by the incorporation of flexible lineages like –O– or –S–.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more researchers have focused on synthesizing new diamine monomers and dianhydride acid monomers because fluorinated monomers cause the polyimide to have a low strength and the performance of the polyimide composites were limited to its compatibility. The side groups, hyperbranched structures, and new diamine monomers containing semifluorinated groups, isopropyl, phenyl phosphyl, and organosilicone have resulted in a large free volume and a decreased dielectric constant. However, monomers have been key in preparing low‐dielectric‐constant polyimides, whereas the previous studies reported dielectric constants from 2 to 3 because the asymmetric structures enhanced the molecular polarity and the monomers were not easily obtained; this limits their applications.…”
Section: Introductionmentioning
confidence: 99%
“…So, the researchers have applied different post‐modification methods to reduce it to a convenient scale. Several methods such as incorporation of porous material into the polymer matrix , thermal degradation of labile graft or block chains in the polyimides , introduction of bulk fluorinated substituents into the polymer backbone , and so forth. were applied to reduce dielectric constant.…”
Section: Introductionmentioning
confidence: 99%